Women's rights as multicultural claims : reconfiguring gender and diversity in political philosophy - Mookherjee, Monica (Edinburgh University Press, 2011)
"Monica Mookerjee reconfigures feminism in a way that responds to cultural diversity, by drawing on Iris Young's idea of 'gender as seriality'. she argues that a discourse of rights can be formulated and that this task is crucial to negotiating a balance between women's interests and multicultural justice." [Publisher's description].